Answer:
x= 0
Step-by-step explanation:
Let's form an equation using the slope of the line.
[tex]\boxed{gradient = \frac{y1 - y2}{x1 - x2} }[/tex]
☆ (x₁, y₁) is the 1st coordinate and (x₂, y₂) is the 2nd coordinate
Let the gradient of line be m.
[tex]m = \frac{5 - 2}{x - 1} [/tex]
[tex]m = \frac{3}{x - 1} [/tex]
The product of the gradients of 2 perpendicular lines is -1.
m(⅓)= -1
[tex]m = - 1 \div \frac{1}{3} [/tex]
m= -1 ×3
m= -3
[tex] - 3 = \frac{3}{x - 1} [/tex]
[tex] - 3(x - 1) = 3[/tex]
[tex]x - 1 = \frac{3}{ - 3} [/tex]
[tex]x - 1 = - 1[/tex]
x= -1 +1
x= 0